2018
DOI: 10.1186/s12885-018-4263-3
|View full text |Cite
|
Sign up to set email alerts
|

Digital breast tomosynthesis for breast cancer screening and diagnosis in women with dense breasts – a systematic review and meta-analysis

Abstract: BackgroundThis study aimed to systematically review and to meta-analyse the accuracy of digital breast tomosynthesis (DBT) versus digital mammography (DM) in women with mammographically dense breasts in screening and diagnosis.MethodsTwo independent reviewers identified screening or diagnostic studies reporting at least one of four outcomes (cancer detection rate-CDR, recall rate, sensitivity and specificity) for DBT and DM in women with mammographically dense breasts. Study quality was assessed using QUADAS-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 31 publications
0
60
0
7
Order By: Relevance
“…There is some evidence to support improved cancer detection (higher sensitivity) and reduced recall rates (specificity) in women with dense breasts screened with DBT relative to DM 14,15 . We did not find any studies comparing findings stratified by breast density for interval cancers identified after DM or DBT.…”
Section: Discussionmentioning
confidence: 67%
“…There is some evidence to support improved cancer detection (higher sensitivity) and reduced recall rates (specificity) in women with dense breasts screened with DBT relative to DM 14,15 . We did not find any studies comparing findings stratified by breast density for interval cancers identified after DM or DBT.…”
Section: Discussionmentioning
confidence: 67%
“…The 3D image allows radiologists to look through the breast, eliminating the influence of superposition (ie, overlapping layers of breast tissue that can obscure the ability to see cancer or give the appearance of an abnormality when none is present). Studies to date trend in the direction of showing that DBT has superior, or at least equivalent, performance compared with 2D mammography in terms of both sensitivity and specificity and appears to have some additional advantages compared with FFDM in screening performance among women with mammographically dense breasts, defined as a mammographic density >50% . A large prospective trial comparing FFDM versus DBT has been launched to determine whether DBT is superior to FFDM in reducing the detection rate of advanced breast cancer…”
Section: Breast Cancermentioning
confidence: 99%
“…Box 1 summarises some of the key scientific facts regarding BD. Early evidence suggests that supplemental (adjunct) screening in women with dense breasts detects additional breast cancers not detected on mammography (4, 15, 16). Specifically, there is early evidence that breast ultrasound and digital breast tomosynthesis detect additional cancers following ‘negative’ mammography screening; estimates of increased cancer detection and the associated increase or decrease in recall rates from supplemental imaging for women with dense breasts varies by imaging modality as summarised in systematic reviews (4, 16).…”
Section: Introductionmentioning
confidence: 99%